Domestic Violence against Women in Indonesia: The Recent Domestic Violence Elimination Law Analysis - Mahfud Mahfud; Rizanizarli Rizanizarli (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
Even though Law Number 23 of 2004 concerning on the Elimination of Domestic Violence was promulgated fifteen years ago, the number of domestic violence against women has not significantly decreased. The Law has not set concrete actions that may fall under the domestic violence that can be punished, particularly in terms of sexual abuse psychological violence, and negligence in household towards women. This research aims to analyze domestic violence against women in this Law and the conducts that are considered to be domestic violence which is commonly found in daily life in Indonesia. A   purely qualitative research method encompassing document analysis of key documents in Indonesia and the Anti-Domestic Violence Law 2004 is adopted in this paper. The research reveals that This Law is particularly protecting women from household violence in Indonesia. The law has recognized physical violence, sexual violence, psychological violence, and negligence as sorts of domestic violence against women in household although it might find difficult to enforce the law when dealing with marital rape regarding lack of reports from victims and polygamy concerning circumstances that can be used to criminalize the perpetrators.